Epigenetics of proteasome inhibition in the liver of rats fed ethanol chronically - Oliva, Joan (The WJG Press and Baishideng, 2009)
AIM: To examine the effects of ethanol-induced proteasome inhibition, and the effects of proteasome inhibition in the regulation of epigenetic mechanisms. METHODS: Rats were fed ethanol for 1 mo using the Tsukamoto-French model and were compared to rats given the proteasome inhibitor PS-341 (Bortezomib, Velcade™) by intraperitoneal injection. Microarray analysis and real time PCR were performed and proteasome activity assays and Western blot analysis were performed using isolated nuclei. RESULTS: Chronic ethanol feeding caused a significant inhibition of the ubiquitin proteasome pathway in the nucleus, which led to changes in the turnover of transcriptional factors, histone-modifying enzymes, and, therefore, affected epigenetic mechanisms. Chronic ethanol feeding was related to an increase in histone acetylation, and it is hypothesized that the proteasome proteolytic activity regulated histone modifications by controlling the stability of histone modifying enzymes, and, therefore, regulated the chromatin structure, allowing easy access to chromatin by RNA polymerase, and, thus, proper gene expression. Proteasome inhibition by PS-341 increased histone acetylation similar to chronic ethanol feeding. In addition, proteasome inhibition caused dramatic changes in hepatic remethylation reactions as there was a significant decrease in the enzymes responsible for the regeneration of S-adenosylmethionine, and, in particular, a significant decrease in the betaine-homocysteine methyltransferase enzyme. This suggested that hypomethylation was associated with proteasome inhibition, as indicated by the decrease in histone methylation. CONCLUSION: The role of proteasome inhibition in regulating epigenetic mechanisms, and its link to liver injury in alcoholic liver disease, is thus a promising approach to study liver injury due to chronic ethanol consumption.